Docking and Structural Modification of Flavonoid Derivative Compounds as Cycloxygenas-2 Enzyme Inhibitors - Tiara Ajeng Listyani; Muniroh Addawiyyah; Danang Raharjo; Pang Jyh Chyang (GLOBAL HEALTH SCIENCE GROUP, 2025)
Seven flavonoid compounds have the activity of inhibiting the cyclooxygenase-2 (COX-2) enzyme, thus providing an anti-inflammatory effect. Molecular docking analysis is needed to determine the binding interaction between flavonoid compounds and the cyclooxygenase-2 (COX-2) enzyme. Objective: This study aims to determine the interaction of flavonoid compounds with the cyclooxygenase-2 (COX-2) enzyme along with the modification of the flavonoid compound structure to increase the binding energy to the cyclooxygenase-2 (COX-2) enzyme. Method: Flavonoid derivative compounds were geometry optimized using VegaZZ software, then target preparation, ligand preparation, docking method validation, and docking analysis were carried out to obtain the interaction between flavonoid compounds and the cyclooxygenase-2 (COX-2) enzyme which is expressed as ∆G and interaction patterns, which include hydrogen bonds, amino acids and functional groups involved, using the program using PyRx-Python 0.8 - AutoDock Vina. Results: The interaction pattern of seven flavonoid derivative compounds with COX-2 enzyme showed hydrogen bonds with amino acids ARG 121, ILE 113, LEU 93, VAL 117. The interaction is similar to the interaction of protoporphrin ix containing co which is the original ligand of the target protein. There is no relationship between the inhibitory activity of flavonoid derivatives and the free energy value of binding (∆G). Modification of the new compound luteolin 7 glucosidase has a better amino acid interaction pattern, namely PRO 155, 154, ARG 44, TYR 131, LEU 153. Conclusions: The binding profile of flavonoid derivatives has the potential to be a candidate for oral cyclooxygenase-2 (COX-2) inhibitor compounds as an anti-inflammatory.